2021
DOI: 10.1186/s10033-020-00528-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Characteristics of Isolated Loaded Tires with Different Tread Patterns: Experiment and Simulation

Abstract: The current research of tire aerodynamics mainly focus on the isolated and simplified tread tire. Compared with the real complex pattern tire, the tread pattern structure and deformed profile of a loaded tire has a greatly influence on tire aerodynamic drag. However, the mechanisms of the isolated loaded tires with different tread patterns effects on the aerodynamic drag are subjects worthy of discussion. The purpose of this study is to experimentally and computationally investigate the aerodynamic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…According to formula (18), EGRA sorting can be performed to obtain optimal solution for comprehensive performance. The design with the highest EGRA value represents the best overall performance.…”
Section: Entropy Weighted Grey Relational Analysis (Egra)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to formula (18), EGRA sorting can be performed to obtain optimal solution for comprehensive performance. The design with the highest EGRA value represents the best overall performance.…”
Section: Entropy Weighted Grey Relational Analysis (Egra)mentioning
confidence: 99%
“…Zhang L X. et al [17] analyzed the influence of the tire profile on the aerodynamic characteristics of the vehicle, established a parametric model based on the tire size parameters, optimized the design parameters of the tire profile, and reduced the aerodynamic resistance. Zhou H C. et al [18] analyzed the influence of tire profile and tread pattern structure on tire aerodynamic performance, studied the load characteristics of different tire pattern structures, and revealed the difference between the flow characteristics and the flow field around the tire. The results show that when the lateral groove angle is in the same direction as the airflow, the tire has less aerodynamic drag.…”
Section: Introductionmentioning
confidence: 99%
“…The surface pressure coefficients were recorded by using an electronic pressure transducer, which includes 2 modules and 128 channels, as shown in Figure 4. There are 15 lateral sections and 4 longitudinal sections in the tire model; each odd lateral section has 7 measuring points, each even lateral section has 6 measuring points, and each longitudinal section has 9 measuring points [25]. The detailed arrangement of pressure measuring points is presented in Figure 5.…”
Section: Wind Tunnel Experimentsmentioning
confidence: 99%
“…The influence of tread pattern grooves on the flow field and aerodynamic drag is revealed by Hobeika and Sebben, 13 the results showed that the edge pattern can induce some small vortices around the contact patch, and these vortices appear to slightly increase the region of flow separation and change the tire drag. Zhou et al 18 carried out the wind tunnel test and CFD simulation to study the influences of the tread pattern of an isolated loaded tire on tire aerodynamic characteristics, and point out that the surface pressure coefficients of the different tread patterns are great different, and the angle of tire transverse grooves has a notable effect on the aerodynamic drag and flow field.…”
Section: Introductionmentioning
confidence: 99%